2019
DOI: 10.1186/s12939-019-1022-2
|View full text |Cite
|
Sign up to set email alerts
|

Through health workers’ eyes: a qualitative study of health service provision for migrants at Schengen border

Abstract: Background Croatia and Slovenia were the transit countries on the Balkan route for migrants and refugees from Middle East countries in 2015 and 2016. They had to optimize health care delivery in the special circumstances in refugee camps and transit centres. Little is known about health care provision in border camps where a large number of migrants stay for only couple of hours. Previous studies emphasize that language barriers and cultural differences play a central part in the relationship betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
(32 reference statements)
3
3
0
2
Order By: Relevance
“… 18 This was exacerbated by the lack of official courses and relevant resources for health professionals to learn about cultural competence in mental health settings. 57 , 63 Moreover, health professionals who feel unequipped to deal with comprehensive needs arising during interactions with immigrant patients have different understandings of mental illness and treatment, 57 , 63 which resonates with our findings. Further, a lack of diversity among healthcare workers and a need for immigrant professionals in mental health and addiction services are well documented in the literature.…”
Section: Discussionsupporting
confidence: 84%
“… 18 This was exacerbated by the lack of official courses and relevant resources for health professionals to learn about cultural competence in mental health settings. 57 , 63 Moreover, health professionals who feel unequipped to deal with comprehensive needs arising during interactions with immigrant patients have different understandings of mental illness and treatment, 57 , 63 which resonates with our findings. Further, a lack of diversity among healthcare workers and a need for immigrant professionals in mental health and addiction services are well documented in the literature.…”
Section: Discussionsupporting
confidence: 84%
“…e results reported from the focus groups and interviews with refugees and health care professionals are not specific to Germany. Our results are comparable to previous research with refugees and health professionals which observed that linguistic and cultural differences are the main barriers for refugees in accessing health care [45,47,48]. e interviewed administrators in our study complemented the perspective of health care professionals.…”
Section: Discussionsupporting
confidence: 89%
“…Chronic hepatitis patients had psychological problems. [ 14 ] Irula people’s perception is very similar with the study findings. Few people believe that spiritual healing is often used to cope with life-altering events such as chronic illness.…”
Section: Discussionsupporting
confidence: 85%